The Development of the Idea of the Inclusion of Children with Special Educational Needs in View of Pre-School Education and Primary School - Elżbieta Jaszczyszyn; Iwona Lewkowicz (Ignatianum University Press, 2017)
Modern views on education have evolved to regard it to be the right of every human being (regardless of gender, nationality, colour of skin, state of health or individual capabilities) to education. In order to provide the best conditions of education for students with various educational needs it is necessary to create a proper climate for working with them at school and in the family environment. What is needed here, is: a) a coalition of all entities responsible for providing psychological-educational assistance for a child and, b) a high level of education offered, c) development of schools and kindergartens, which will properly satisfy the needs of children with special educational needs. In this process it is necessary to create the legal basis for such actions, a climate of social acceptance, preparation of teachers and other staff working in educational institutions and organizing conditions and situations for direct contacts and interactions of children of diverse needs and development capabilities. Mutual relations can be maintained in a climate of acceptance, understanding, joy and sense of one's personal development. Inclusive education is our hope for providing able-bodied students and students with special educational needs the sense of belonging to the same community, which is a school/kindergarten as well as to a globally organized human civilization. Keywords: inclusion, inclusive education, special educational needs, kindergarten, school.